2023
DOI: 10.1007/s13762-023-04791-2
|View full text |Cite
|
Sign up to set email alerts
|

Are the ecotoxicological tools viable to evaluate the effectiveness of wastewater treatment plant effluents?

Abstract: Ecotoxicological tools have proved to be sensitive and appropriate for the evaluation of the effectiveness of treatments used in wastewater treatment plants (WWTP). The objective of this study was to assess the applicability of bioassays and biomarkers to evaluate the efficiency of different treatments throughout WWTP samples[A—raw influent, B—preliminary effluent, C—final effluent, and D—receiving stream], seasonally over 1 year, through a multispecies approach: i) bacterial cell viability [Escherichia coli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Different bacteria were found across all the sampling sites, including sampling site C, which corresponded to the effluent after the MBR treatment with an ultrafiltration process. The presence of antibiotic-resistant isolates from the entrance to the exit of the WWTP was in agreement with previous reports, which indicated that the MBR treatment applied was insufficient to reduce the microbial load [18]. This reinforces the need to apply additional strategies at this WWTP to ensure the proper removal of microorganisms, which may require the development of novel technologies and procedures [34].…”
Section: Isolation Results and Identificationsupporting
confidence: 90%
See 1 more Smart Citation
“…Different bacteria were found across all the sampling sites, including sampling site C, which corresponded to the effluent after the MBR treatment with an ultrafiltration process. The presence of antibiotic-resistant isolates from the entrance to the exit of the WWTP was in agreement with previous reports, which indicated that the MBR treatment applied was insufficient to reduce the microbial load [18]. This reinforces the need to apply additional strategies at this WWTP to ensure the proper removal of microorganisms, which may require the development of novel technologies and procedures [34].…”
Section: Isolation Results and Identificationsupporting
confidence: 90%
“…Wastewater samples were collected in May 2021 and in July 2021 from four different points within a wastewater treatment plant located in the northern region of Portugal (the WWTP features are detailed in reference [18]). The four sampling points represented: A-raw influent of untreated wastewater; B-preliminary effluent already treated for the removal of coarse solids, sands, oils and fats; C-final effluent after membrane bioreactor (MBR) treatment with an ultrafiltration process but before the discharge in the river; and D-the stream receiving the WWTP effluent [18]. Samples were collected in 100 mL sterile flasks and kept in cold conditions until they were processed.…”
Section: Sampling and Processingmentioning
confidence: 99%
“…Lemna minor growth inhibition assays were conducted according to standard guidelines (OECD, 2006), with microplate adaptation (Diogo et al, 2023). Four replicates per elutriate were used, and in each replicate 12.5 mL of elutriate and four fronds of L. minor were added.…”
Section: Lemna Minor-growth Inhibition Assaymentioning
confidence: 99%
“…Catalase (CAT) represents one of the first enzymes involved in the antioxidant defense system (responsible for the catalysis of hydrogen peroxide, a reactive oxygen species that if not eliminated or neutralized by antioxidant defenses can induce oxidative stress, in water) (Alkimin et al, 2020). On the other hand, malondialdehyde (MDA) is a final product of lipid peroxidation, that can be used as an important indicator of physiological stress (Diogo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at , File S1: metadata for Figures S1–S4 (main text); Figure S5: 3-parameter log-logistic concentration–response model fittings of RGR frond ; Figure S6: 3-parameter log-logistic concentration–response model fittings of F v /F o ; Figure S7: 3-parameter log-logistic concentration–response model fittings of Y(II); and Table S1: The results of the 3-parameter log-logistic model fittings with calculated EC 20 and EC 50 values for the studied endpoints. References [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ,…”
mentioning
confidence: 99%